1999
DOI: 10.1080/095006999290778
|View full text |Cite
|
Sign up to set email alerts
|

Scope, sequence and coordination: The Iowa Project, a national reform effort in the USA

Abstract: Two sections of middle school science were taught by two longtime teachers where one used an STS approach and the other followed the more typical textbook approach closely. Pre-and post assessments were administered to one section of students for each teacher. The testing focused on student concept mastery, general science achievement, concept applications, use of concepts in new situations, and attitudes toward science. Videotapes of classroom actions were recorded and analyzed to determine the level of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 14 publications
3
41
0
10
Order By: Relevance
“…Taiwan Modules on light, electricity, and nuclear energy formed the focus of the study Yager and Weld (1999) Scope, Sequence and Continuity (SS&C), a 5-year context-based course for students aged 11 -16 USA Lubben et al (1997) Matsapha project materials taught to students aged 13 -14…”
Section: Irelandmentioning
confidence: 99%
“…Taiwan Modules on light, electricity, and nuclear energy formed the focus of the study Yager and Weld (1999) Scope, Sequence and Continuity (SS&C), a 5-year context-based course for students aged 11 -16 USA Lubben et al (1997) Matsapha project materials taught to students aged 13 -14…”
Section: Irelandmentioning
confidence: 99%
“…Thus, there is an urgent need of methodologically more rigorous research in this field in the first place. Yager and Weld (1999), evaluating the so called Iowa SS&C project (scope, sequence and coordination) on a large scale, found the STS-orientated approach to be superior in comparison to textbook-orientated lessons in terms of teachers confidence and constructivist attitudes as well as student achievement (d = 1.52; as reported in Bennett et al 2007). The intervention programme lasted about 4 years.…”
Section: Contexts In Science Education-empirical Findingsmentioning
confidence: 99%
“…The investigation of Yager and Weld (1999) lasted about 4 years and revealed an effect size of d = 1.52 (strong effect; Cohen 1988); Winther and Volk's (1994) nearly yearlong study showed a medium-sized effect of d = 0.63; students in Fechner's study experienced context-based learning in an experimental setting on five subsequent days and revealed small to medium-sized effects regarding achievement (η 2 = 0.02 to 0.08), whereas Kölbach's 2-day intervention showed no significant results. A possible reason for this timedependence might be that the impact of context-based learning on students' conceptual understanding, mediated by students increasing interest and/or motivation, only comes into effect with larger time scales.…”
Section: Contexts In Science Education-empirical Findingsmentioning
confidence: 99%
“…A literate person should display understanding of the main science concepts, principles, and theories, ability to put into practice some science processes, and positive attitudes toward STS issues, which include knowledge about the main features of S&T as ways of knowing (epistemology), understanding S&T as human enterprises (social aspects), and some understanding of the history of S&T (Aikenhead, 1994b;Yager & Weld, 1999). Achieving positive attitudes toward S&T is one of the most broadly recognised innovations in science education, which echo the reform goal of switching from the traditional S&T education for the future scientific elite to a new S&T education for all citizens, and is closely tied to the personal and social relevance of S&T, and the decision making on public techno-scientific issues (Désautels & Larochelle, 2003;Roth, 2002;Zeidler, 2003).…”
Section: Introductionmentioning
confidence: 99%